Commynes – Mémoires: l’émancipation syntactico-sémantique à l’origine d’un genre ? - Dupuy, Estéle (Romanica Silesiana, 2021)
Was the Commynes’s syntactic cohesion (a man “not literary”, father of the genre of memoirs and diplomat of the fifteenth century which syntax has been often described as paratactic or uncohesive) influenced, according to the received idea, by his habit of the diplomatic despatch and was she perceived as uncohesive by his contemporaries? To answer his questions, respectively, we compare the lack of cohesion of the Memoirs with those of his autograph letters and then we search the headlines of the publisher Sauvage (1552) who propose a version pointed as more cohesive than that of the manuscript which serve of base to his edition. The results will show that the letters seem more cohesive than the Memoirs and that its Mémoirs’ s syntax is not underlined as embarrassing by its editor.